PUSAT REMAJA BANJARBARU - Ulvia, Rifda; Sarbini, Gusti Novi (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Banjarbaru is a developing city, also known as the City of Students, where this is of course closely related to students, the majority of whom are teenagers, which then become the nation's potential and assets as the next generation to continue development. Banjarbaru Youth Center is a public open space to accommodate teenagers so they can learn and develop in a positive and healthy environment. In this design, the authors uses park as an open space for adolescents as an answers to design problems by using the third place method so that the design elements are personalized to the conditions, needs, and activities in accordance with the characteristics of today's youth to be able become a space of expression place for adolescents to doing activities and develop in a social and environmentally friendly space.